2022
DOI: 10.31235/osf.io/y83ze
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Perceived Workplace Bureaucracies on Self-Evaluated Efficacy, Job Satisfaction and Motivation in the Workplace during the COVID-19 Pandemic

Abstract: Workplace bureaucracies impact many areas of an employee’s working life. High levels of perceived bureaucracy can diminish employees’ job motivation, satisfaction, and performance. During the COVID-19 pandemic, infection containment measures likely contributed to the factors underlying the “great resignation” via the lack of self-efficacy from perceived bureaucracy. Recruiting 240 full-time employees between late 2021 to early 2022 across organizations in both private and public sectors, the Work Extrinsic Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
0
0
Order By: Relevance
“…While it was previously reported that women tend to be more religious and have more involvement in matters of the faith (de Vaus & McAllister, 1987), this study was in line with a more recent ( 2008) study finding the lack of gender effects (Simpson et al, 2008). This was consistent with the lack of gender effects found for many measured psychological parameters such as in perceived bureaucracy (Kang, 2022), perhaps reflecting equality in gender treatment.…”
Section: Lucksupporting
confidence: 91%
“…While it was previously reported that women tend to be more religious and have more involvement in matters of the faith (de Vaus & McAllister, 1987), this study was in line with a more recent ( 2008) study finding the lack of gender effects (Simpson et al, 2008). This was consistent with the lack of gender effects found for many measured psychological parameters such as in perceived bureaucracy (Kang, 2022), perhaps reflecting equality in gender treatment.…”
Section: Lucksupporting
confidence: 91%
“…This might be due to the complexity of the modern world, the diminishing reliance on instincts, and the presence of institutions such as the education system that emphasize duty, obedience, and hierarchy instead of self-organization and cooperation. The bureaucratic nature of modern systems might also contribute to a sense of reduced control, as indicated by the negative correlation between perceived workplace bureaucracy and self-efficacy (Kang, Tay & Gan 2022). External Locus of Control beliefs, which refer to the perception that external-factors have greater influence over one's life, have been associated with depression and stress (Twenge, Zhang and Im 2004).…”
Section: Feeling Of Controlmentioning
confidence: 99%